Integration Between Customary Law and National Law: An Effort to Build a Pancasila Prismatic Law State - Sihotang, Amri Panahatan; Chansrakaeo, Ruetaitip (SASI, 2023)
Introduction: This article to examine and analyze aspects of integration between national law and customary law in the context of the prismatic Pancasila state law, especially after the enactment of the draft criminal code (RKUHP) as a law.                                                                                             Purpose of The Research: This research seeks to answer two problem formulations, namely: integration of customary law and national law in the Pancasila law state and how are efforts to organize harmonious relations between customary law and national law in the perspective of the prismatic Pancasila state law, especially after the ratification of the RKUHP.Methods of Research: This study uses normative legal research methods based on authoritative legal products in the form of laws and regulations. The analysis was carried out by prioritizing the concept approach, historical approach, and statutory approach.                                                               Result of The Research: Even though customary law and national law are different in substance and character, but customary law and national law must be integrated because have important relations in relation to practice in society. Efforts to organize a harmonious relationship between customary law and national law in the perspective of the Pancasila prismatic state law, especially after the ratification of the RKUHP by optimizing the three year transitional provisions in the RKUHP to socialize as well as determining steps and efforts that can guarantee harmonious relations between customary law and national law.